The Spectrum of Tuberculosis Disease in an Urban Ugandan Community and Its Health Facilities. (6th December 2020) - Kendall, Emily A; Kitonsa, Peter J; Nalutaaya, Annet; Erisa, K Caleb; Mukiibi, James; Nakasolya, Olga; Isooba, David; Baik, Yeonsoo; Robsky, Katherine O; Kato-Maeda, Midori; Cattamanchi, Adithya; Katamba, Achilles; et al.
Abstract: Background: New, sensitive diagnostic tests facilitate identification and investigation of milder forms of tuberculosis (TB) disease. We used community-based TB testing with the Xpert MTB/RIF Ultra assay ("Ultra") to characterize individuals with previously undiagnosed TB and compare them to those from the same community who were diagnosed with TB through routine care. Methods: We offered community-based sputum Ultra testing to adult residents of a well-defined area (population 34 000 adults) in Kampala, Uganda, via door-to-door screening and venue-based testing, then used detailed interview and laboratory testing to characterize TB-positive individuals. We compared these individuals to residents diagnosed with pulmonary TB at local health facilities and a representative sample of residents without TB (controls). Results: Of 12 032 residents with interpretable Ultra results, 113 (940 [95% confidence interval CI, 780–1130] per 100 000) tested positive, including 71 (63%) positive at the lowest (trace) level. A spectrum of TB disease was observed in terms of chronic cough (93% among health facility–diagnosed cases, 77% among residents with positive community-based Ultra results at levels above trace, 33% among trace-positive community participants, and 18% among TB-negative controls), TB symptom prevalence (99%, 87%, 60%, and 38%, respectively), and C-reactive protein (75th percentile: 101 mg/L, 28 mg/L, 6 mg/L, and 4 mg/L, respectively). Community-diagnosed cases were less likely than health facility–diagnosed cases to have human immunodeficiency virus coinfection or previous TB. The specificity of Ultra was 99.4% (95% CI, 99.2%–99.5%) relative to a single spot sputum culture. Conclusions: People with undiagnosed prevalent TB in the community have different characteristics than those diagnosed with pulmonary TB in health facilities. Newer diagnostic tests may identify a group of people with early or very mild disease. Abstract : Community-based tuberculosis testing with Xpert MTB/RIF Ultra revealed prevalent disease that was milder and potentially more prolonged compared to routinely diagnosed tuberculosis from the same community. Trace-positive Xpert Ultra results were common, but the specificity of community-based testing exceeded 99%.